Two‐dimensional location of moving targets within local areas using WiFi‐based multistatic passive radar. Issue 2 (1st February 2014) - Falcone, Paolo; Colone, Fabiola; Macera, Antonio; Lombardo, Pierfrancesco
Abstract : In this study the authors investigate the two‐dimensional target localisation capabilities of a passive radar system based on WiFi transmissions. It is well known that the most straightforward way to achieve the target position estimation in the horizontal plane with a passive radar exploits the measurements either of a single bistatic range plus a direction of arrival (DoA) or of two bistatic ranges collected by two separate receivers. However, for a practical application it is interesting to clearly define which one of the two approaches provides the passive radar target localisation with a higher accuracy and whether combining both multiple bistatic range plus DoA measurements provides a further advantage. A multistatic configuration is considered which allows to collect a set of range/Doppler/angle measurements for a given target. Different target localisation strategies are devised and compared, based on subsets of the available measurements with the aim of understanding the localisation accuracies achievable using the different combinations of measurements. Experimental results are shown based on a passive radar prototype developed and fielded at the DIET Department – Sapienza University of Rome. This will contribute to demonstrate the fruitful application of the passive radar concept for short range surveillance.